IMPLEMENTASI PROGRAM JAMSOSRATU DALAM BIDANG KESEHATAN DI KABUPATEN PANDEGLANG - Devi Triady Bachruddin; Agus Sjafari (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2018)
Poverty in Banten province is still a serious problem that should be addressed by the local government. The efforts to resolve is implementing Program Jaminan Sosial Rakyat Banten Bersatu (Jamsosratu). The purpose of this research is focused on the implementation of Jamsosratu Program in health sector in Pandeglang District, with case studies on Mekarjaya and Pandeglang sub-districts. Researcher use the implementation model of Van Meter and Van Horn as theoretical approach and qualitative approach as research method. Data collected through observation and in-depth interviews. The results of this research show that the implementation of Jamsosratu Program in Pandeglang and Mekarjaya sub-districts has been reachedbased on the size and policy objectives. The Attitudes of Jamsosratu program implementers, especially on counselors at the kecamatan level is passive to do mentoring. Communication and co-ordination of counselors are less proactive with the sub-district, puskesmas, poskesdes and midwives or posyandu. The result shows that social aspect, economic and political environment strongly supports the implementation of the Jamsosratu Program.